1998
DOI: 10.1007/s003830050274
|View full text |Cite
|
Sign up to set email alerts
|

Operative complications of hernia repair in childhood

Abstract: In a training center, 1,131 inguinal hernias were repaired in 1,000 consecutive patients in 6 years. The documents of these patients were reviewed retrospectively for surgical complications. A total of 38 complications were encountered in 35 patients, including wound infection (1.9%), recurrence (0.9%), tethered testis (0.3%), bladder injury (0.3%), was deferens injury (0.2%), iatrogenic orchiectomy (0.1%), and postoperative death. Most of them occurred in the early years of the clinic, and nearly one-half wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 5 publications
3
19
1
Order By: Relevance
“…12,13 Regarding age distribution significant patients were presented under one year of life. In our study Haematoma was more commonly noticed in 9 (5 %) patients in the De Lange et al study and Farhat et al study, 12,13 haematoma was found in 14,15,16 Ein and colleagues reported 1.2 % of wound infection in their study. 17,18,19 There was no mortality this study.…”
Section: Discussionsupporting
confidence: 49%
“…12,13 Regarding age distribution significant patients were presented under one year of life. In our study Haematoma was more commonly noticed in 9 (5 %) patients in the De Lange et al study and Farhat et al study, 12,13 haematoma was found in 14,15,16 Ein and colleagues reported 1.2 % of wound infection in their study. 17,18,19 There was no mortality this study.…”
Section: Discussionsupporting
confidence: 49%
“…Recurrences are rare complications, typically seen in less than 1 % of elective hernia operations in our clinic which is similar to the literature [1][2][3][4]. In extraordinary circumstances, such as strangulated hernia operations, ascites, and ventriculoperitoneal shunts, the recurrence rate can increase up to 24 % [5].…”
Section: Introductionsupporting
confidence: 51%
“…For a similar class of wounds in the industrialized countries [2,11] and in some emerging economies [12,13], the postoperative wound infection rate was said to be very low. That wound infections occurred mainly in the control group when compared with the antibiotic group, as well as the statistical significance showed that the absence of postoperative wound infection in the antibiotic group was probably due to prophylactic use of gentamicin in the group.…”
Section: Discussionmentioning
confidence: 99%